tRNA epitranscriptomics and biased codon are linked to proteome expression in Plasmodium falciparum - Dedon, Peter C. (2019)
Among components of the translational machinery, ribonucleoside modifications on tRNAs are emerging as critical regulators of cell physiology and stress response. Here, we demonstrate highly coordinated behavior of the repertoire of tRNA modifications of Plasmodium falciparum throughout the intra‐erythrocytic developmental cycle (IDC). We observed both a synchronized increase in 22 of 28 modifications from ring to trophozoite stage, consistent with tRNA maturation during translational up‐regulation, and asynchronous changes in six modifications. Quantitative analysis of ~2,100 proteins across the IDC revealed that up‐ and down‐regulated proteins in late but not early stages have a marked codon bias that directly correlates with parallel changes in tRNA modifications and enhanced translational efficiency. We thus propose a model in which tRNA modifications modulate the abundance of stage‐specific proteins by enhancing translation efficiency of codon‐biased transcripts for critical genes. These findings reveal novel epitranscriptomic and translational control mechanisms in the development and pathogenesis of Plasmodium parasites.